Combining DNA and protein alignments to improve genome annotation with LiftOn - Chao, Kuan-Hao; Heinz, Jakob M.; Hoh, Celine; Mao, Alan; Shumate, Alaina; Pertea, Mihaela; Salzberg, Steven L. (Genome Research, 2025)
As the number and variety of assembled genomes continue to grow, the number of annotated genomes is falling behind, particularly for eukaryotes. DNA-based mapping tools help to address this challenge, but they are only able to transfer annotation between closely related species. Here we introduce LiftOn, a homology-based software tool that integrates DNA and protein alignments to enhance the accuracy of genome-scale annotation and to allow mapping between relatively distant species. LiftOn's protein-centric algorithm considers both types of alignments, chooses optimal open reading frames, resolves overlapping gene loci, and finds additional gene copies when they exist. LiftOn can reliably transfer annotation between genomes representing members of the same species, as we demonstrate on human, mouse, honeybee, rice, and Arabidopsis thaliana. It can further map annotation effectively across species pairs as far apart as mouse and rat or Drosophila melanogaster and Drosophila erecta.